NON-PARTICIPATORY OBSERVATION OF INTEGRATED MANAGEMENT OF CHILDHOOD ILLNESS PRACTICES AT SELECTED BASIC HEALTH UNITS OF DISTRICT ABBOTTABAD, KP, PAKISTAN: A QUALITATIVE HERMENEUTIC STUDY - Abrar, Saidul; Assad Hafeez; Muhammad Naseem Khan; Sana Rahim; Yasir Ali; Rubina Bibi (Journal of Ayub Medical College Abbottabad, 2023)
Background: It was in 1995 when a strategy was devised with the intent to reduce under-five mortality in countries having a prevalence of child mortality above 40/1000 live births. This strategy is called integrated management of childhood illness (IMCI). Improvement in the skills of healthcare workers (HCWs) depends on the IMCI training received by them. To make IMCI training more effective and scale up, a global technical consultation committee in Geneva recommended implementing an innovative training approach in 2014: the distance learning IMCI (dIMCI). This study was conducted to observe qualitatively the practices of IMCI-trained HCWs at their respective workplaces. Methods: This qualitative hermeneutic study was conducted through non-probability criterion sampling in the district Abbottabad of Pakistan on all 26 basic health units trained in IMCI (either standard or distance learning) from December 9, 2019, to March 9, 2020. Data collection was done by qualitatively observing consultations and interactions of caretakers of under-five children at basic health units. Inductive thematic analysis was used. This qualitative exploration was underpinned by Hans Georg Gadamer’s philosophy of hermeneutics. Results: Four themes emerged from the observation notes. These themes are gratification after consultation, altercation for medication, non-observance of protocol, and methodical consultation. Conclusion: Improvement in the skills of HCWs in the form of IMCI training, either through distance learning or the common eleven-day standard method, can improve caretakers’ satisfaction. However, awareness at the community level is needed for better compliance.